PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI INTERPERSONALTERHADAP MOTIVASI KERJA KARYAWAN DI UPTD LABORATORIUM KONSTRUKSI DAN BANGUNAN DINAS PUPR PROVINSI BENGKULU - Ades Panja Neto; Merta Kusuma (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the "Influence of Leadership Style and Interpersonal Communication on Employee Work Motivation at the Construction and Building Laboratory Technical Implementation Unit (UPTD), Public Works and Housing Agency, Bengkulu Province," both partially and simultaneously. The type of research used is quantitative research. The population in this study amounted to 30 people, using the total side technique, which means the entire population is used as the research sample. Based on the t-test on the leadership style variable, it is known that the calculated t value > t table (5.535 > 1.697) with a probability of t sig 0.000 < 0.05. On the interpersonal communication variable, the calculated t value > t table (3.641 > 1.697) with a probability of t sig 0.001 < 0.05. So it can be concluded that both X variables, namely leadership style and interpersonal communication, partially influence employee performance. Based on the results of the f test, it is known that the calculated f value > f table (22,688 > 3.34) with a probability of f sig 0.000 < 0.05, which indicates that Ho is rejected and Ha is accepted, meaning that leadership style and interpersonal communication simultaneously have a positive effect on performance variables. The R square value obtained is 62.7%, which means it has a strong influence. This figure shows that employee performance can be explained by leadership style and interpersonal communication by 82.7%. The remaining 37.3% is influenced by other factors not examined or explained in this study. Keywords: Compensation, Motivation and Employee Performance